A pain in the neck. (14th October 2011) - Minns, Tania; Raj, Ray; Clark, Kate
Abstract : A 21-year-old man presented to the emergency department with pain and swelling to the right side of his neck and chest wall with associated shortness of breath. Two days earlier, while playing football, he had been involved in a minor collision with another player where he was struck on the right side of his head, but had managed to continue playing. On examination, the patient had extensive cervical surgical emphysema. There were no further positive findings on respiratory and general examination. A chest x-ray demonstrated no rib or clavicular fractures and no pneumothorax. Therefore, a CT was undertaken to ascertain the cause of the surgical emphysema. This demonstrated a pneumomediastinum, pneumopericardium and extradural air in the spinal column in addition to the subcutaneous air. The CT identified no bony trauma and no other injuries. The symptoms resolved spontaneously and follow-up radiography, 9 days later, showed no residual air.